Threatened gastropods under the evolutionary genetic species concept: redescription and new species of the genus Aylacostoma (Gastropoda: Thiaridae) from High Paraná River (Argentina–Paraguay) - Vogler, Roberto E. (2014)
The genus Aylacostoma Spix, 1827, is mainly endemic to South America, and comprises about 30 nominal species, most of which were described based solely on conchological features following the typological approaches of most of the 19th and the mid-20th century authors. Here, we redescribe Aylacostoma chloroticum Hylton Scott, 1954, and describe Aylacostoma brunneum sp. nov. from the High Paraná River (Argentina–Paraguay) by means of morphological and molecular characters. Both are threatened species currently included into an ongoing ex situ conservation programme, as their habitats have disappeared because of damming and the filling up of the Yacyretá Reservoir in the early 1990s. We used DNA sequences from cytochrome b and cytochrome oxidase subunit I (COI) genes to estimate their genetic distances, and the COI sequences were also used to assess their specific status under the evolutionary genetic species concept by means of the K/θ method. Our results clearly demonstrate that both must be recognized as evolutionary genetic species, despite only minor differences in morphological characters other than in the shells.